Developing a mobile augmented reality for facilitating socio-scientific issue-based biology learning - Diqna Nur Annisa; Agung Wijaya Subiantoro (Biosfer: Jurnal Pendidikan Biologi, 2023)
This study is research and development using modified design and development research (D&DR) model through three main phases: 1) design; 2) development; and 3) evaluation with the aim of establishing an instructional product for teaching and learning. Augmented reality technology was used to develop a Mobile Augmented Reality of Respiratory System (MARRS) which was proposed for conducting socio-scientific issue-based biology learning on the topic of respiratory system. The MARRS was designed to visualize the context of smoking. More specifically, students were able to observe the structure and function of the respiratory system, simulation of smoking effects on lungs, and lung’s disorder affected by smoking. Research findings show that there are three main aspects to be considered as the framework of the MARRS development: (1) the system design; (2) features; and (3) how to incorporate the MARRS into SSI-based biology learning. Once the MARRS was developed, it went through several round of validations by experts, practitioner, and users to evaluate its properness for teaching and learning. According to the validation criteria, the MARRS was categorized as very good in general. It can be concluded that the MARRS is proper to be implemented in teaching and learning of the respiratory system topic.